Systematic Literature Review on Coronavirus Infectious Disease-19 and Dental Masks - Ji-Hyun Kim; Min-Young Kim (The Korean Society of Dental Hygiene Science, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted primarily through droplets, and dental practitioners are at risk of occupational exposure to SARS-CoV-2 infection owing to direct contact with the patient's mouth, aerosols from dental procedures, and saliva. Wearing a mask is believed to be the best method of protection against infection, and a systematic literature review was conducted on whether the dental masks used in dentistry are effective in preventing Coronavirus Infectious Disease-19 (COVID-19).Methods: We used PubMed, Google Scholar, DBpia, NDSL, and KISS databases for this study. Of the 917 documents narrowed down by the search terms "Coronavirus, COVID-19, and dental," 83 documents were collected and studied. Ultimately, 42 of these papers were selected for analysis after considering duplication from the flow chart of the literature selection process.Results: While dental masks are often used when treating patients with unknown COVID-19 status, the Ministry of Food and Drug Safety stated that the use of dental masks is insufficient in preventing cross-transmission of COVID-19; instead, it was recommended that N95 masks, which correspond to KF94 masks, should be worn daily. On the other hand, wearing a dental mask and following precautions such as hand hygiene may not pose a significantly higher risk of infection than wearing an N95 mask when treating COVID-19 patients.Conclusion: There is an ongoing discussion regarding the use of dental masks when treating dental patients, and many argue that different types of masks should be selected according to the degree of infection and the individual's respiratory condition. By considering the safety and efficacy of dental masks in preventing infection, improvements can be made in the management of COVID-19 and dental-related infections.